COVID-19 and the Gaping Wounds of South Africa’s Suboptimal Immunisation Coverage: An Implementation Research Imperative for Assessing and Addressing Missed Opportunities for Vaccination - Chukwudi A. Nnaji; Charles S. Wiysonge; Maia Lesosky; Hassan Mahomed; Duduzile Ndwandwe (Vaccines, 2021)
Despite South Africa’s substantial investments in and efforts at ensuring universal access to immunisation services, progress has stalled and remains suboptimal across provinces and districts. An additional challenge is posed by the ongoing coronavirus disease 2019 (COVID-19) pandemic, which has disrupted immunisation services globally, including in South Africa. While there is growing evidence that missed opportunities for vaccination (MOV) are a major contributor to suboptimal immunisation progress globally, not much is known about the burden and determinants of MOV in the South African context. Herein, we make a case for assessing MOV as a strategy to address current immunisation coverage gaps while mitigating the adverse impacts of the COVID-19 pandemic on immunisation services. We illustrate a practical implementation research approach to assessing the burden of MOV among children in primary care settings; for understanding the factors associated with MOV; and for designing, implementing, and evaluating context-appropriate quality improvement interventions for addressing missed opportunities. Such efforts are vital for building health system resilience and maintaining immunisation programme capacity to optimally deliver essential health services such as routine childhood immunisation, even during pandemics.